Educação em direitos humanos e ensino de lígua inglesa : possibilidade da abordagem CLIL - Correia, Danieli Spagnol Oliveira (2018)
The main objective of this study is to verify possibilities and limitations of the teaching of Human Rights through English as an additional language, within the Content and Language Integrated Learning (CLIL) approach. To this end, the study examines the appropriation of pre-service teachers of English as regards CLIL in the production of their teaching plans with themes related to Human Rights Education (HRE) through English. With that aim, a diagnostic questionnaire was developed and administered at the beginning of the first semester to students (pre-service teachers) in the English Practicum course to verify their prior knowledge of the CLIL approach and HRE. During the semester, the teacher/researcher assisted in the elaboration of teaching plans. Data also includes field notes and interviews carried out in the format of conversation circle during the discipline. The theoretical assumptions include official documents on HRE, the concepts of English-language critical education (PENNYCOOK, 2001), as well as Freire’s pedagogy (1998). The research methodology is qualitative and categorized as a case study inspired in autoethnography (SANTOS, 2017). The data analysis suggests that the appropriation of the CLIL and EDH approaches is evidenced in relation to the theoretical assumptions.